Research on high‐pressure abrasive water jet slotting and pressure relief technology for hard rock roof - Huang Zhenfei; Wu Wenbin (Energy Science & Engineering)
Abstract To solve the problem of severe rock pressure near coal mining face tunnels, a high‐pressure abrasive water jet slotting and roof breaking pressure relief technology is proposed. First, the laneway deformation mechanism and the process of hard rock slotting using high‐pressure abrasive water jets under long‐distance cantilever conditions are analyzed, and the crack initiation conditions of roof strata are obtained. Second, slotting tests under different slotting pressures, nozzle diameters, abrasive particle sizes and slotting times were carried out, and the slotting parameters of a high‐pressure abrasive water jet on a typical roof rock were obtained. Finally, industrial application was carried out in the 81,403 working face of Huayang No.1 Mine. After the hydraulic roof slotting measures were implemented in the test area, the maximum axial force of the anchor cable was reduced to 67 kN, which was 35.5% lower than that of the comparison. The average stress of the coal seam was 15 MPa, which was approximately 25% lower than that of the comparison. The deformation of the tunnel in the experimental area was significantly controlled, with an average movement of 30.0% toward the roof and floor of the tunnel and an average movement of 23.2% toward the two sides of the tunnel. Compared with the movement in the comparison section, the movement toward the roof and floor of the laneway was 42.3% lower, and the movement toward the two sides was 38.2% lower. The industrial application results show that high‐pressure abrasive water jet roof slotting and pressure relief technology can cut off the stress transmission path between the roof rock on both sides, effectively improve the stress state of the surrounding rock of the laneway, reduce the deformation of the roof, floor and two sides of the working face in the later stage of the mining laneway.